Highly stretchable, ionic conductive and self‐recoverable zwitterionic polyelectrolyte‐based hydrogels by introducing multiple supramolecular sacrificial bonds in double network. Issue 29 (28th March 2019) - Diao, Wenjing; Wu, Linlin; Ma, Xiaofeng; Zhuang, Zhenzhen; Li, Shuai; Bu, Ximan; Fang, Ying
ABSTRACT: Zwitterionic hydrogels have been explored for applications in electrochemical devices very recently due to their high water retention ability and interesting electrochemical properties. The use of zwitterionic hydrogels in devices requires them tough and recoverable or healable from fatigue damage. Herein, a double network zwitterionic hydrogel contains a reversible noncovalent interaction crosslinked polyvinyl alcohol (PVA) first network, together with a covalent/noncovalent hybrid crosslinked acrylamide and sulfobetaine methacrylate copolymer (P(AM‐ co ‐SBMA)) second network, was fabricated by a simple two‐steps methods of copolymerization and freezing/thawing. The reversible hydrogen bonds, crystalline domain, and electrostatic interactions in the double networks work as sacrificial bonds to dissipate energy and toughen the materials when hydrogel deforms. The broken bonds can reform upon unloading endowing the recovery of hydrogels' properties with the assistance of the elastic covalent network. The optimal hydrogels are highly stretchable (fracture strain 970%), tough (fracture toughness 693 kJ m −3 ), rapidly recoverable (65% toughness recovery and 75% stiffness recovery after resting 5 min at room temperature) and with widely tunable mechanical properties by multibond crosslinking. Meanwhile, the zwitterionic counterions of SBMA moieties endow the tough and recoverable hydrogels extremely high intrinsic ionic conductivities (7.49 S m −1 ) at room temperature. This work not only provides a simple strategy for fabricating tough and recoverable zwitterionic hydrogels but also demonstrates multifunctional properties of the zwitterionic hydrogels, which possess a great potential to fulfill flexible devices applications. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47783. Abstract :